2013
DOI: 10.1007/s12687-012-0133-x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards prenatal diagnosis and abortion in a multi-ethnic country: a survey among parents of children with thalassaemia major in Malaysia

Abstract: Thalassaemia is a public health problem in multiethnic Malaysia which mainly affects the Malays, KadazanDusuns and Chinese. This study, the first in Malaysia, aims to evaluate the acceptability of prenatal diagnosis and abortion among Malaysian parents who have a child or children with thalassaemia major and the socio-demographic factors affecting their decision-making. A pre-structured questionnaire was distributed to parents of children with thalassaemia major. Response rate for completed surveys was 99.1 %.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 12 publications
2
30
1
Order By: Relevance
“…A total of 74.8% of the parents interviewed did not want to terminate the pregnancy. This is not surprising as similar study conducted in Malaysia (a multiethnic country) also found that 73.4% of Muslim participants were against termination compared with 25% of Christians and 13.3% of Buddhists . Deafness was rated high for TOP, especially among mothers.…”
Section: Discussioncontrasting
confidence: 99%
“…A total of 74.8% of the parents interviewed did not want to terminate the pregnancy. This is not surprising as similar study conducted in Malaysia (a multiethnic country) also found that 73.4% of Muslim participants were against termination compared with 25% of Christians and 13.3% of Buddhists . Deafness was rated high for TOP, especially among mothers.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, an average of 2,000 bags of blood are needed to treat almost 1,000 patients throughout the nation daily (Bernama, 2015). This follows various reports that about 3%-5% or 1 in 20 (1.5 million) Malaysians are estimated to be carriers of the thalassaemia gene, an inherited disease of blood disorder requiring regular blood transfusions (The Star, 2010;Ngim et al, 2013). The national blood requirement is also exacerbated by the lack of donors during various festive and school holidays observed seasonally in Malaysia, although recent proactive measures undertaken by the Malaysian National Blood Centre has improved the situation (Lim, 2014;Wooi Seong, Raffeal and Ayob, 2014).…”
Section: Introductionsupporting
confidence: 76%
“…Studies on genetic diseases, such as fragile X syndrome, Down syndrome and cystic fibrosis, suggest that parents with affected children have various attitudes toward PGT and continuation/termination of affected pregnancies (24)(25)(26)(27)(28)(29)(30). Many factors are associated with parents' decision-making, including, but not limited to, religion, disease severity, testing procedures, psychological conditions, family-related factors, gestation period while undergoing the test, and previous experience with the disease (26)(27)(28)(29)(31)(32)(33).…”
mentioning
confidence: 99%